Curcumin as a Holistic Treatment for Tau Pathology - Sivanantharajah, Lovesha; Mudher, Amritpal (Frontiers in Pharmacology, 2022)
Global forecasts for prevalence of Alzheimer’s Disease (AD) estimate that 152.8 million people will have dementia in 2050, rising sharply from 57.4 million in 2019 (GBD 2019). This rise can be attributable to increases in population growth and aging, but in the absence of disease-modifying therapies it poses a huge societal challenge that must be addressed urgently. One way to combat this challenge is to explore the utility of holistic treatments that may protect against AD, including traditional herbs, spices and other nutraceuticals that are pharmacologically safe, inexpensive and readily available. In this light, the spice Turmeric, and its active ingredient Curcumin, has been investigated as a potential holistic treatment for AD over the last two decades. However, promising results with animal studies have not translated to success in clinical trials. One issue is that most animal models examining the effects of curcumin and curcumin derivatives in AD have been done with a focus at ameliorating amyloid pathology. Due to the limited success of Amyloid-β-based drugs in clinical trials, tau-focused therapeutics provide a promising alternative. In this review article, our focus is to provide a clearer picture of what is currently known about the effectiveness of curcumin and curcumin derivatives to ameliorate tau pathology. Tau focused studies may help inform more successful clinical studies by placing greater emphasis on the development and optimised delivery of curcumin derivatives that more effectively target tau pathology.